The need to quantify authors’ relative intellectual contributions in a multi-author paper - Rahman, Mohammad Tariqur; Mac Regenstein, Joe; Abu Kassim, Noor Lide; Haque, Nazmul (Elsevier, Ltd., 2017)
Measuring the contribution of each author of a multi-author paper has been a long standing concern. As a possible solution to this, we propose a list of intellectual activities and logistic support activities that might be involved in the production of a research paper. We then develop a quantitative approach to estimate an author's relative intellectual contribution to a published work. An author's relative intellectual contribution is calculated as the percent contribution of an author to each intellectual activity involved in the production of the paper multiplied by a weighing factor for each intellectual activity. The relative intellectual contribution calculated in this way can be used to determine the position of an author in the author list of a paper. Second, a corrected citation index for each author, called the T-index, can be calculated by multiplying the relative intellectual contribution by the total citations received by a paper. The proposed approach can be used to measure the impact of an author of a multi-authored paper in a more accurate way than either giving each author full credit or dividing credit equally. Our proposal not only resolves the long standing concern for the fair distribution of each author's credit depending on his/her contribution, but it will also, hopefully, discourage addition of non-contributing authors to a paper.